Precision evaluation of nitrogen isotope ratios by Raman spectrometry. Issue 9 (17th October 2022) - Yamamoto, Junji; Hagiwara, Yuuki
Abstract: We measured Raman spectra of N2 fluids obtained at 0.1–25 MPa at room temperature. The 14 N 15 N peak in the Raman spectrum of a low‐pressure N2 fluid is difficult to detect because of the prevalence of a group of peaks attributed to rotational vibration of 14 N2 . The Raman peaks of 14 N 15 N and 14 N2 of N2 fluid at 25 MPa were acquired at various exposure times. The mean values and standard deviations of the peak height ratios and peak area ones of 14 N 15 N and 14 N2 were examined for each time. The standard deviations of the peak height ratios and peak area ones were 2.2% and 1.9%, respectively, for 20 spectra acquired with peak height of 1 million counts of 14 N2 . The uncertainties are about two times higher than those predicted from the noise of a CCD. Improvement of the pixel resolution can enhance the precision of the nitrogen isotope ratios by Raman spectroscopy.